An Unbiased Reexamination of Stock Market Volatility - Mankiw, N. Gregory; Romer, David; Shapiro, Matthew D. (Journal of Finance, 1985)
Recent work demonstrates serious statistical problems with standard volatility tests. This paper proposes new tests that are unbiased in small samples and that do not require assumptions of stationarity. The new tests continue to find evidence against the model positing rational expectations and a constant required rate of return on equity.